The Conscripting System in Armed Forces: Turkey's Example - (:unkn) unknown (ELSEVIER SCIENCE BV, 2015)
In the armed forces of Turkey the compulsory service is the valid system. This is how temporary privates are obtained from among healthy and young male citizens. They constitute the backbone of the military man power; their numbers attain figures much bigger than the numbers of rank-carrying personnel, namely commissioned-officers and petty-officers. It is a widely known fact that military life is indeed tough, especially for those occupying the lower levels within the hierarchical pyramide. Conventionally those conscripts have their own informal ways to cope with the mentioned hardships. Effective seniority circles and Landsman solidarity are two most commonly observed practices, despite the rigid forbidding regulations of the official policy. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: Seniority; compatriot; conscript; draft; private; rank; army; service